Strategi Manjemen Media Online dI Masa Pandemi COVID-19 - Nihayah, Izzatin; Rachmiatie, Atie; Rinawati, Rini (Jurusan Ilmu Komunikasi, Fakultas Dakwah dan Komunikasi, UIN Sunan Gunung Djati Bandung, 2024)
The COVID-19 pandemic is a major disaster for all sectors in Indonesia, including the media business. The media must be able to survive and continue to provide news in the midst of a pandemic. The purpose of this research is to discuss the analysis of strengths and weaknesses, to know planning patterns in reporting online media, to know and to analyze the steps for organizing online media planning and to know and to analyze why reporting strategies must be carried out during a pandemic. In this study used a qualitative method with a case study approach. The data collection technique is through in-depth interviews, observation and document tracing. This research resulted in strengths and weaknesses in news management during a pandemic, namely easy-to-access online media, increased readers on the jabar.tribunnews.com website, and has loyal readers. The downside is that access requires a smartphone and internet network, there is a decrease in revenue due to reduced advertisers and the reporting process uses applicable regulations (Health Protocol). There are four stages of the Management Process, namely Planning, Organizing, Actuating and Controlling in the reporting process. The reporting process consists of five processes, namely news planning, news search, news writing, news editing, and news publishing. The background of the change in management strategy is that there are internal factors, namely communication and employees and also external factors, namely decreased income, the economy and also government regulations.